여기까지: Korean as a foreign language learning fossilization among adult Filipinos - Galang, Aljon Delmo (Universitas Pendidikan Indonesia (UPI), 2022)
Language fossilization happens when learners do not progress anymore in certain features of the target language, especially in interlanguage learning context. this investigation sought to answer the following research questions: (a) What are the linguistic features in Korean language that the KFL Filipino learner participants are fossilized in? (b) Why do they arrive at such state of fossilization?. The qualitative study used narrative approach to identify the linguistic features that the KFL Filipino learner participants are fossilized in, and the reasons behind such language phenomenon, based on their learning narratives. There were twelve (12) KFL Filipino learners who participated in the study. Their narratives on KFL learning were analyzed, coded, and arranged to identify these fossilizations and the reasons behind. Findings reveal that the KFL (a) fossilizations are in sound-character correspondence, orthographical-phonological metamorphosis, language syntax, verb conjugation and suffixation in context, and vocabulary difficulty and (b) the reasons of fossilization are weak memory, language disorder, Hangeul character resemblance and subtle differences, differences of L1 and L2 sentence patterns to Korean language syntax, lack of interest on sources of language exposure, discourse opportunities with Korean language speakers, and fear of language use due to uncertainty. These results contribute to improvement of foreign language instruction.